2022
DOI: 10.1038/s41598-022-08162-8
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose multi-detector computed tomography for periradicular infiltrations at the cervical and lumbar spine

Abstract: Periradicular infiltrations are frequently performed in daily neuroradiological routine and are often guided by multi-detector computed tomography (MDCT), thus leading to radiation exposure. The purpose of this study was to evaluate MDCT with low dose (LD) and model-based iterative reconstruction for image-guided periradicular infiltrations at the cervical and lumbosacral spine. We retrospectively analyzed 204 MDCT scans acquired for the purpose of cervical or lumbosacral periradicular interventions, which wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…From this point of view, pre-biopsy imaging should be carefully reviewed and when possible focused on the definite region of biopsy, together with an optimized radiation dose. This approach is similar to a recent study investigating LD protocols for CT-guided periradicular infiltrations 33 . However, biopsies use hardware for puncture of the target region with comparatively large calibers (e.g., potential risk for more pronounced artifacts especially with LD protocols) that often need to be inserted deeper into tissue (e.g., close to the nerve root in periradicular infiltrations versus biopsies of vertebral bone), making distinct investigations for biopsies necessary in the light of patient safety and sufficient image quality.…”
Section: Discussionsupporting
confidence: 57%
“…From this point of view, pre-biopsy imaging should be carefully reviewed and when possible focused on the definite region of biopsy, together with an optimized radiation dose. This approach is similar to a recent study investigating LD protocols for CT-guided periradicular infiltrations 33 . However, biopsies use hardware for puncture of the target region with comparatively large calibers (e.g., potential risk for more pronounced artifacts especially with LD protocols) that often need to be inserted deeper into tissue (e.g., close to the nerve root in periradicular infiltrations versus biopsies of vertebral bone), making distinct investigations for biopsies necessary in the light of patient safety and sufficient image quality.…”
Section: Discussionsupporting
confidence: 57%
“…Excluding LD simulations, reported dose reductions ranged from 34% in 204 PRI patients [ 60 ] up to 93% in 183 cervical PRI patients [ 59 ] and 94% in 65 sacroiliac joint injection patients [ 55 ]. The use of LD protocols did not meaningfully affect the rate of complications [ 54 , 55 , 58 ] or patient-reported pain [ 53 , 59 , 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…After implementation of an LD protocol with tube currents reduced from 40 mA to 20–30 mA, a study in 204 patients observed no relevant difference in IQ or nerve root determination. The reported dose reduction of 34% did not affect the confidence for both planning and performing PRIs at the cervical and lumbosacral spine [ 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation